Four Kinds of Intention: Actual, Habitual, Virtual, and Interpretative - Penner, Sydney (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
Suárez distinguishes between four different ways of intending an end of action: actually, virtually, habitually, and interpretatively. This distinction comes to be repeated in scores of books and articles in subsequent centuries as a standard part of action theory, and Suárez is evidently the source for many of the later authors. This paper examines Suárez’s treatment of the distinction. Interpretative intention receives the most attention, since Suárez appears to give several inconsistent characterizations of it in different works. The paper ends with some notes about the subsequent reception of the distinction and reflects briefly on the lessons to be drawn about tracing Suárez’s influence.